Customary Land Governance Transformation and Indigenous Public Administration in Border Communities of East Nusa Tenggara - Mariayani O. Rene; Syukur Muhaymin Adang Djaha; Ernestus Holivil; Belandina Long (Universitas Medan Area, 2026)
This study examines the transformation of customary (ulayat) rights into individual ownership and its implications for land governance in border communities of East Nusa Tenggara, focusing on Wehali Village, Malaka Regency. Existing studies have primarily examined customary land issues from legal, agrarian, and anthropological perspectives, while limited attention has been given to how the conversion of communal rights into individual ownership affects governance legitimacy and institutional authority in indigenous border communities. Wehali was selected as a strategic case because it remains a major center of customary governance in Timor while experiencing increasing interaction with state-led land administration reforms. Using a qualitative case study approach, data were collected through in-depth interviews, participant observation, and document analysis involving customary leaders, community representatives, and government actors. The findings show that customary institutions continue to regulate communal land through traditional leadership structures such as Liurai, Loro, Nain, and Fukun. However, the expansion of formal land certification has shifted authority toward legal-rational administrative systems that prioritize individual ownership. This transformation has generated institutional dualism, governance fragmentation, declining compliance with adat norms, and uncertainty in land governance. The study further reveals that the sustainability of customary land governance depends on institutional resilience, community compliance, and state recognition. The novelty of this research lies in conceptualizing customary land transformation as a governance transition process and proposing an Integrated Governance framework in which collaborative governance mediates the relationship between customary legitimacy and formal administrative authority. The study contributes to Indigenous Public Administration by demonstrating that indigenous institutions perform key public administration functions related to resource management, dispute resolution, participation, and collective decision-making. The findings highlight the importance of collaborative governance and participatory land administration for sustainable governance in indigenous border regions.